Climate change cannot be entirely responsible for soil carbon loss observed in England and Wales, 1978-2003 - SMITH, PETE; CHAPMAN, STEPHEN J; SCOTT, W. ANDY; BLACK, HELAINA I.J; WATTENBACH, MARTIN; MILNE, RONNIE; CAMPBELL, COLIN D; LILLY, ALLAN; OSTLE, NICK; LEVY, PETER E; LUMSDON, DAVID G; MILLARD, PETER; et al. (Global change biology, 2007)
We present results from modelling studies, which suggest that, at most, only about 10-20% of recently observed soil carbon losses in England and Wales could possibly be attributable to climate warming. Further, we present reasons why the actual losses of SOC from organic soils in England and Wales might be lower than those reported.